The PENERAPAN PERAWATAN KATETER DENGAN CHLORHEXIDINE DISINFEKTAN UNTUK MENCEGAH TERJADINYA RISIKO INFEKSI SALURAN KEMIH PADA PASIEN CEREBRO VASCULER ACCIDENT (CVA) DI RUANG ICU RSUD DR. (H.C.) IR.SOEKARNO PROVINSI BANGKA BELITUNG: PENERAPAN PERAWATAN KATETER DENGAN CHLORHEXIDINE DISINFEKTAN UNTUK MENCEGAH TERJADINYA RISIKO INFEKSI SALURAN KEMIH PADA PASIEN CEREBRO VASCULER ACCIDENT (CVA) DI RUANG ICU RSUD DR. (H.C.) IR.SOEKARNO PROVINSI BANGKA BELITUNG - Ponika; Eny Erlinda Widyaastuti; Dudella Desnani Firman Yasin (Journal of Nursing Care and Biomolecular, 2023)
Cerebro Vascular Accident (CVA) is a condition when blood flow to the brain is interrupted due to a blockage or rupture of a blood vessel which results in compressed brain tissue resulting in herniation. Clinical symptoms in CVA include paralysis of the limbs, experiencing weakness, limited range of motion and decreased muscle strength. CVA patients will experience ineffective cerebral tissue perfusion which can cause a decrease in consciousness. Decreased awareness of CVA will experience conditions in the long term and incontinence will occur so that a catheter is attached. One of the interventions performed was Catheter Care with Chlorhexidine. The purpose of this case study is to describe the application of catheter care with disinfectant Chlorhexidine to prevent the risk of urinary tract infection in Cerebro Vascular Accident (CVA) patients. The design of this scientific paper uses the approach of 2 patients diagnosed with CVA. This research method is descriptive in the form of a case study approach by applying nursing interventions based on practical evidence. Methods of data collection were carried out through participatory observation, structured interviews, documentation, literature studies. The results of the case study showed that catheter care with Chlorhexidine for 3 consecutive days could prevent the risk of infection. The conclusion obtained is that the application of catheter care with Chlorhexidine disinfectant in Cerebro Vascular Accident (CVA) can prevent the risk of urinary tract infections related to catheter insertion. Keywords: Cerebro Vascular Accident (CVA), Chlorhexidine 2%, Catheter Care.